Ecological Grouping of Nematodes of Nut Crops in the Surkhandarya Region of Uzbekistan - Saidova Elmira Anvarovna; Norbabaeva Saodat Tovoshovna; Bekmurodov Abdujabbor Sattorovich (Peerian Journals Publishing, 2022)
The article provides data on the fauna of phytonematodes in the root soil and the root system of nut crops in the conditions of the Surkhandarya region of Uzbekistan. As a result of the research, 76 species of plant nematodes belonging to 46 genera, 30 families, 9 orders and 2 subclasses were identified. The fauna of phytonematodes of walnut crops was dominated by species Heterocephalobus elongatus, H.filiformis, Acrobeloides nanus, Chiloplacus propinquus, Panagrolaimus rigidus, Rhabditis brevispina, R.filiformis, Aphelenchus avenae, Filenchus filiformis and Meloidogyne incognita.
Keywords: nut crops; phytonematodes; Surkhandarya region; detachment